1994
DOI: 10.1002/hep.1840190104
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes: An investigation of type-specific differences in geographic origin and disease

Abstract: Because of the nucleotide sequence diversity of different isolates of hepatitis C virus, it has become important to clarify whether distinct genotypes of hepatitis C virus vary with respect to pathogenicity, infectivity, response to antiviral therapy and geographic clustering. We assessed nucleotide sequence variability in the 5' noncoding region of hepatitis C virus, using restriction enzymes to analyze the distribution of hepatitis C virus genotypes, in 80 patients with chronic hepatitis C virus infection. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(97 citation statements)
references
References 40 publications
6
86
0
5
Order By: Relevance
“…6 The evolution of various genotypes is influenced by infection patterns, population migration, immune selection, and replication efficiency. 7,8 …”
Section: Molecular Biology Of Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…6 The evolution of various genotypes is influenced by infection patterns, population migration, immune selection, and replication efficiency. 7,8 …”
Section: Molecular Biology Of Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…However, while some genotypes are ubiquitous, others are found only in specific regions, where they exhibit a high diversity of subtypes (Figure 2). This distribution pattern and the antigenic and biological differences between the HCV types point to long periods of endemic infection during which there was no significant exchange with types from other regions[42]. …”
Section: Resultsmentioning
confidence: 99%
“…In North America, parts of South America, United Kingdom, Scandinavia and Australia, 1a is the most prevalent subtype[42]. In Greece, Poland and the Netherlands, subtype 3 is responsible for 30% of all cases, and in Russia and the Baltic States, subtypes 1b and 3a share dominance[48].…”
Section: Resultsmentioning
confidence: 99%
“…Other associations between HCV genetic variation and pathology are less well accepted. Some studies found little evidence for virulence differences between the major HCV genotypes [39], [40], but most studies found differences, such as genotype 1 being more virulent than genotype 2 [41], [42]. Most studies have found genotype 1b to be more virulent and more highly associated with HCC than other genotypes [43][47].…”
Section: Introductionmentioning
confidence: 99%